THE IMPACT OF THE FINANCIAL RATIOS AS THE MEASUREMENT UPON THE PERFORMANCE OF RETURN ON ASSETS AT THE PUBLIC BANKS IN INDONESIA (The Empiric Study upon The Banking Companies Registered at BEI in 2012-2015) - Gilang Ramadhan Fajri (The Accounting Journal of Binaniaga, 2017)
This research is an empiric study about The Impact of The Financial Ratios as The Measurement upon The Performance of Return on Assets of Public Banks In Indonesia (The Empiric Study upon The Banking Companies Registered at BEI in 2012-2015), sampling technique being used is purposive sampling which is the total samples of 30 companies. The aims of this study is to prove that the impact of financial ratios refers to Capital Adequacy Ratio (CAR), Operational Cost comparing to the Operational Revenue (BOPO), Net Interest Margin (NIM), Non Performing Loan (NPL) neto and Loan to Deposit Ratio (LDR) against the banks performance measured by Return On Asset (ROA) and which variable has been affecting the most dominant upon Return On Assets (ROA). The analysis technique being applied is multiple linear regression and the hypothesis test using t-statistics to examine a partial regression coefficient and f-statistics to examine the compliance of the research model refers to the level of significance 5%. Furthermore, the research has applied the classical assumption test covering normality test, multicollinierity test, heteroxedasity test and auto-correlation test.Keywords : Capital Adequacy Ratio (CAR), the Operational cost comparing to the operational revenue (BOPO), Net  Interest Margin (NIM), Non Performing Loan (NPL) Neto, Loan to Deposit Ratio (LDR), Return On Asset (ROA).